"En fullkomlig man": Kropp och samhällsutveckling hos Viktor Rydberg - Sjödin, Alfred (Tidskrift för litteraturvetenskap, 2021)
“The Complete Man”: Body and Society in Viktor Rydberg The article treats the place of the body in the cultural criticism of Viktor Rydberg, not only as a central theme but also as an image with the potential to figuratively describe societal and even cosmic relationships. Rydberg’s ideal of the symmetrical and athletic body is seen in the perspective of his dependence on German neo-humanism and the gymnastic movement. The ideal of bodily symmetry figures as an image of universal man who defies the division of labor, while the deformed body inversely figures as an image of the lack of wholeness in a stratified bourgeois society. This is further elucidated by an analysis of Rydberg’s view of Darwinism and his fear of degeneration. In the final section, special attention is given to Rydberg’s broodings on the “Future of the White Race”. In this text, the body is a figure of the collectivity (the body politic) and its diseases signify political and moral crisis, while the remedy for this state of affairs lies in recognizing the unity of the living, the dead and the unborn in the body of Christ.